Competency Certification Of Sewing Graduates Of Children And Adults Clothing In Anggrek Courses And Training Institutions Padang - Dewi Rahayu; Alim Harun Pamungkas (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
This study was motivated by Anggrek’s competency certification agency (LKP) which has B accreditation and its competency has been valid at the ASEAN level (Malaysia, Singapura, Thailand, Vietnam, etc.) This study is aimed to determine the competency certification and competence of the trainees at LKP Anggrek Padang, especially to describe the benefits of certification of the competence of the trainees. This study using qualitative research method using a case study approach. According to Cresewell (2010) qualitative research has its own character. This means that qualitative research is carried out in natural setting and the writer is used as the main instrument in research activities and data collection focus on meaning according to participant words. The source data of this study are; LKP supervisor, instructors, and training assistants and participants. Techniques of data collection used in this study were interviews, observation, and documentation. The validity of the data of this study is used triangulation of data sources. The result of this study are; (1) competency certification can be obtained by training participants by fulfilling certain stages, participating in training activities with predetermined time, (2) competency of training participants can be seen by conducting competency test activities.Keywords: competency certification, competency of trainee